2014
DOI: 10.1016/j.celrep.2014.06.028
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil NLRC4 Inflammasome Selectively Promotes IL-1β Maturation without Pyroptosis during Acute Salmonella Challenge

Abstract: The macrophage NLRC4 inflammasome drives potent innate immune responses against Salmonella by eliciting caspase-1-dependent proinflammatory cytokine production (e.g., interleukin-1β [IL-1β]) and pyroptotic cell death. However, the potential contribution of other cell types to inflammasome-mediated host defense against Salmonella was unclear. Here, we demonstrate that neutrophils, typically viewed as cellular targets of IL-1β, themselves activate the NLRC4 inflammasome during acute Salmonella infection and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
370
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 352 publications
(417 citation statements)
references
References 50 publications
28
370
3
4
Order By: Relevance
“…In B cells infected with Salmonella Typhimurium ΔsopB , we observed re-establishment of IL-Iβ secretion; surprisingly, these cells did not undergo pyroptosis (Figure S8). A similar event has been observed in neutrophils and primary human monocytes infected with Salmonella ; these cells secreted IL-1β without undergoing pyroptosis [6,50]. These results support the idea that IL-1β secretion might be a pyroptosis-independent mechanism.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In B cells infected with Salmonella Typhimurium ΔsopB , we observed re-establishment of IL-Iβ secretion; surprisingly, these cells did not undergo pyroptosis (Figure S8). A similar event has been observed in neutrophils and primary human monocytes infected with Salmonella ; these cells secreted IL-1β without undergoing pyroptosis [6,50]. These results support the idea that IL-1β secretion might be a pyroptosis-independent mechanism.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to macrophages, other cells of the immune system are targets of this pathogen, including dendritic cells and neutrophils [6,7]. Furthermore, we and others have reported that B cells are also a target of Salmonella [8–12].…”
Section: Introductionmentioning
confidence: 99%
“…Gram-negative Salmonella spp, which cause typhoid fever and gastroenteritis, is one such example of an intracellular bacterium. Several studies have demonstrated clear functions for inflammasomes in controlling the replication of Salmonella, through cytokine activation and induction of pyroptosis [16,23,24].…”
Section: Pyroptosis As a Pathogen Clearance Mechanismmentioning
confidence: 99%
“…Pyroptosis of infected cells is emerging as an important mechanism of microbial clearance [24], in addition to host defence mechanisms coordinated by inflammasomedependent IL-1β [16], and IL-18 [23,25]. Macrophage pyroptosis releases Salmonella from its intracellular replicative niche, and increases its susceptibility to neutrophil-mediated extracellular destruction (Figure 1).…”
Section: Pyroptosis As a Pathogen Clearance Mechanismmentioning
confidence: 99%
See 1 more Smart Citation